2010
DOI: 10.5688/aj740583
|View full text |Cite
|
Sign up to set email alerts
|

Low Vision Simulator Goggles in Pharmacy Education

Abstract: Objective. To develop simulator goggles that produce disease-specific characteristics of selected low vision conditions for use in pharmacy education. Methods. Individual sets of simulator goggles were developed for glaucoma, cataracts, macular degeneration, diabetic retinopathy, and retinitis pigmentosa. Students rated the presence and severity of disease-specific characteristics after wearing each pair of goggles while manipulating medicationrelated materials. Results. One hundred students completed the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…To the best of our knowledge, there is no validated scoring system to address the difficulty rating. We chose to use the 4-point Likert-type scale as this was the method used in the Zagar and Baggarly 4 study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there is no validated scoring system to address the difficulty rating. We chose to use the 4-point Likert-type scale as this was the method used in the Zagar and Baggarly 4 study.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that low-vision simulator goggles can reliably simulate the symptoms of common ocular conditions. 3,4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from investigations of emergency scenarios, there has also been research on simulating eye diseases in recent years, albeit primarily for educational purposes: Zagar et al [35] developed individual sets of (non-VR) goggles to simulate glaucoma, cataracts, macular degeneration, diabetic retinopathy, and retinitis pigmentosa, and used them to rate the presence and severity of disease-specific characteristics. Similarly, Wood et al [32] used modified goggles in a study to investigate the effects of simulated visual impairments on nighttime driving performance and pedestrian recognition under real-road conditions.…”
Section: Previous Work On Simulating Vision Impairmentsmentioning
confidence: 99%
“…The low-vision goggles used in the activity have been previously described. 27 The objectives for the learning series were for students to: (1) recognize challenges encountered by older adults with low-vision conditions; (2) compare and contrast medication management difficulties among low-vision conditions; (3) differentiate medication management difficulties of individual low-vision conditions; and (4) propose solutions to prescription drug information access problems for patients with low vision.…”
Section: Designmentioning
confidence: 99%